Effect of surcharge pressures and moisture contents on the pipe jacking force / Elbis Shuhaimi Zakaria - Zakaria, Elbis Shuhaimi (1991)
Trenchless pipe laying or pipe jacking is a-new technique of pipe laying being carried out in Malaysia. Its many advantages may override its disadvantages in many casses. However very little study have been carried to gather information regarding the technique. This small study will provide a basis of understanding of the pipe jacking process. However the study is limited to some soil parameters only. The soil used in this testing was of the laterite type. The pipe used was of a 150 mm diameter asbestos concrete pipe . As moisture contents and surcharge(depth of soil) have an effect on the jacking force, the relationship between the jacking force and the distance travelled with moisture content and surcharge are presented in this report. The variation of the jacking force and the distance travelled with four different surcharges and same moisture content is highlighted. Test were also conducted for five different at same surcharge moisture contents is also provided. A total of 20 tests were carried out.